Differences in fluorodeoxyglucose positron emission tomography/computed tomography findings between elderly onset rheumatoid arthritis and polymyalgia rheumatica. Issue 4 (July 2015) - Takahashi, Hiroyuki; Yamashita, Hiroyuki; Kubota, Kazuo; Miyata, Yoko; Okasaki, Momoko; Morooka, Miyako; Takahashi, Yuko; Kaneko, Hiroshi; Kano, Toshikazu; Mimori, Akio
Abstract Objectives. To compare the fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) findings in patients with elderly-onset rheumatoid arthritis (EORA) with those in patients with polymyalgia rheumatica (PMR), two conditions with similar clinical presentations. Methods. We retrospectively analyzed the FDG-PET/CT findings in 10 patients with EORA and 27 patients with PMR admitted to our department between 2006 and 2012. Results: No significant difference was observed in the median patient ages at the time of FDG-PET/CT scans in the EORA and PMR groups (73.5 vs. 78.0 years, respectively). Significant differences in both FDG uptake scores and standardized uptake values were observed between the two groups in the ischial tuberosities, spinous processes, and wrists. No significant differences were detected in the shoulders and hips. However, specific uptake patterns were observed in each group: circular and linear uptake patterns were observed around the humeral head in the EORA group, whereas focal and non-linear uptake patterns were observed in the PMR group. Moreover, focal uptake in front of the hip joint, indicating iliopectineal bursitis, tended to be limited to the PMR group. High sensitivity (92.6%) and specificity (90%) were observed for PMR diagnoses when at least three of the following five items were satisfied: characteristic findings of shoulder and iliopectineal bursitis, FDG uptake in ischial tuberosities and spinal spinous processes, and lack of FDG uptake in the wrists. Conclusion. The differences in the degree of uptake at each lesion and in uptake patterns at the shoulders and hips are potentially useful for obtaining a definitive diagnosis.